2002
DOI: 10.2134/jeq2002.1880
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ash Application on Cadmium Concentration in Small Mammals

Abstract: ABSTRACTthe effects of pollutants, a factor neglected in many investigations.In order to assess the effects of wood ash application to forests on small mammals, we collected bank voles (Clethrionomys glareolus ) and common shrews (Sorex araneus ) from a forest area in southern MATERIALS AND METHODS Finland. Part of the sample population was from sites that had been Three study plots treated with ash and two control plots treated with ash 1.5 years earlier, part from untreated control sites.with no ash applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
0
5
0
2
Order By: Relevance
“…Ogoshi et al (1992) confirmed that Cd has a lesion effect on the mechanical strength of bone, for both young and old rats. Effects of raised concentrations of Cd in small mammals are also discussed by Ma et al (1991), Leffler and Nyholm (1996), Nickelson and West (1996), and Lodenius et al (2002b) It appears that the food source of the animals could be of great importance, as discussed by Lodenius et al (2002b) The difference in Cd concentrations following WAA between the bank voles and the common shrews ( Sorex araneus ) in that study could be explained by different food habits. The seasonal variations of Cd concentrations in plants (Lodenius, 2002) or other food sources, might also explain differences in Cd amounts in animals and should be considered when planning experiments with WAA.…”
Section: Biotoxic Effects Of Wood Ash Applicationmentioning
confidence: 58%
“…Ogoshi et al (1992) confirmed that Cd has a lesion effect on the mechanical strength of bone, for both young and old rats. Effects of raised concentrations of Cd in small mammals are also discussed by Ma et al (1991), Leffler and Nyholm (1996), Nickelson and West (1996), and Lodenius et al (2002b) It appears that the food source of the animals could be of great importance, as discussed by Lodenius et al (2002b) The difference in Cd concentrations following WAA between the bank voles and the common shrews ( Sorex araneus ) in that study could be explained by different food habits. The seasonal variations of Cd concentrations in plants (Lodenius, 2002) or other food sources, might also explain differences in Cd amounts in animals and should be considered when planning experiments with WAA.…”
Section: Biotoxic Effects Of Wood Ash Applicationmentioning
confidence: 58%
“…The results may thus possibly be affected by seasonal variations in environmental Cd concentration (cf. Lodenius, 2002;Lodenius et al, 2002). Insects were collected both passively with pitfall traps and manually.…”
Section: Insect Samplesmentioning
confidence: 99%
“…A recent meta-analysis has reported that biochar addition to soil generally reduces short-term concentrations of NH 4 + -N and NO 3 − -N (Nguyen et al 2017). Wood ash, in some circumstances, may contain elevated concentrations of trace elements, which raises concerns regarding its use as a soil amendment (Bramryd and Fransman 1995;Lodenius et al 2002;Aronsson and Ekelund 2004;Augusto et al 2008). Most jurisdictions have established criteria to evaluate the suitability of wood ash intended for use as soil amendments (Haglund 2008;Ribbing and Bjurström 2011;Hannam et al 2016).…”
Section: Introductionmentioning
confidence: 99%